LA TUTELA, PROMOCIÓN Y AMPLIACIÓN DE LOS DERECHOS LINGÜÍSTICOS COMO FACTOR PROMOTOR DE IDENTIDAD ÉTNICA Y NACIONAL EN PERÚ: PROTECTION, PROMOTION AND EXTENSION OF LANGUAGE RIGHTS AS A PROMOTING FACTOR OF ETHNIC AND NATIONAL IDENTITY IN PERU - Bermúdez Tapia, Manuel (2020)
The recognition of multiculturalism, multilingualism, and the historical cultural condition of Peru is an issue that has not yet acquired the importance itof rights because a country cannot be built based on the exclusion of certain population groups. should have on the political agenda. Proof of this is that there is no State Policy, or public policies, that complement each other in the care of indigenous communities to generate a progressive, autonomous and democratic protection of rights. Public policies must be evaluated from this perspective of protection, promotion and expansion of rights because a country cannot be built based on the exclusion of certain population groups.